Impact of exogenous zeatin on the growth, pigment complex and capacity of sporophytes of Salvinia natans (Salviniaceae) for biological extraction of zinc from the water - Kosakivska I.V.; Vasyuk V.A.; Shcherbatiuk M.M.; Voytenko L.V.; Romanenko K.O. (Ukrainian Botanical Journal)
The response of plants to heavy metals involves phytohormones, particularly cytokinins, with zeatin being one of the active forms. Exogenous phytohormones are believed to induce plant resistance to heavy metals and enhance phytoextraction. We investigated the impact of exogenous zeatin on the morpho-physiological characteristics of young and mature sporophytes of Salvinia natans and their ability to extract zinc ions from the aquatic environment. It has been shown that zeatin mitigated the adverse effect of zinc sulfate on dry weight accumulation, but did not alleviate its negative impact on fresh weight accumulation in both young and mature sporophytes. During intensive growth and sori formation and spore maturation stages under zinc loading, exogenous zeatin (at 10–6 M concentration) led to 40% and 50% increase in the dry weight of young and mature sporophytes, respectively. In the presence of zinc sulfate, the total chlorophyll content decreased by 23% in the fronds of young sporophytes and by 44% in the fronds of mature sporophytes, while total carotenoids decreased by 21% in both cases. Zeatin addition alleviated the negative impact of the metal on the pigment complex in young sporophyte fronds but exacerbated it in mature sporophyte fronds. The pigment complex of the sporophyte was more susceptible to metal action during sori formation and spore maturation, resulting in frond browning and pronounced chlorosis. However, chlorosis was less intense and localized upon zeatin addition. The capacity of S. natans sporophytes to extract zinc ions from the aqueous medium was demonstrated, with zinc concentration decreasing by over tenfold from 10 mg·L–1 to 0.6 mg·L–1after 14 days of cultivation. The application of zeatin did not affect the efficiency of zinc ions extraction from water.